2021
DOI: 10.1182/blood-2021-151826
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Blinatumomab with Reduced Intensity Chemotherapy in the Treatment of Older Adults with Newly Diagnosed Ph Negative B-Precursor Acute Lymphoblastic Leukemia - Interim Analysis of the Australasian Leukemia and Lymphoma Group ALL08 Study

Abstract: The advent of pediatric inspired regimens has improved the outcome for younger adults with Acute Lymphoblastic Leukemia (ALL), however this comes at a considerable toxicity burden limiting its applicability in older adults. The advent of novel immunotherapies, such as Blinatumomab, an anti-CD19 targeting Bi-specific T-cell engager, has improved outcomes for adults with relapsed refractory and minimal residual disease (MRD) positive B-precursor (BCP) ALL. The Australasian Leukemia and Lymphoma Group (ALLG) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…The trial ALL08 reported 53 episodes of sepsis, infection or febrile neutropenia and 1 grade 3 CRS versus 2 episodes of sepsis and infectious shock and no grade 3 CRS in our study. Moreover, no incidence of neurotoxicity was reported in our study compared with seven episodes in the ALL08 study 16 and one episode of neurological disorder in the D‐ALBA study 9 . The incidence of overall grade 3 events was also less in our study (8 events) compared with the D‐ALBA study (21 events).…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…The trial ALL08 reported 53 episodes of sepsis, infection or febrile neutropenia and 1 grade 3 CRS versus 2 episodes of sepsis and infectious shock and no grade 3 CRS in our study. Moreover, no incidence of neurotoxicity was reported in our study compared with seven episodes in the ALL08 study 16 and one episode of neurological disorder in the D‐ALBA study 9 . The incidence of overall grade 3 events was also less in our study (8 events) compared with the D‐ALBA study (21 events).…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, in another clinical trial of chemotherapy combined with blinatumomab, ALL08, the chemotherapy dose was not substantially reduced, and hence, the incidence of chemotherapy-related AEs remained high. 16 The trial ALL08 reported 53 episodes of sepsis, infection or febrile neutropenia and 1 grade 3 CRS versus 2 episodes of sepsis and infectious shock and no grade 3 CRS in our study. Moreover, no incidence of neurotoxicity was reported in our study compared with seven episodes in the ALL08 study 16 and one episode of neurological disorder in the D-ALBA study.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…3C). Other studies have also examined the role of adding blinatumomab to chemotherapy in patients with Ph-negative ALL, reporting similarly promising early results (Table 1) [71][72][73].…”
Section: Ph-negative Adult Pre-b All (Age Up To 60 Years)mentioning
confidence: 97%
“…Similarly, the EWALL-BOLD trial evaluates replacing the second cycle of intensive induction chemotherapy with blinatumomab followed by sequential chemotherapy and further blinatumomab cycles to treat elderly ALL patients [45]. Apart from that, inotuzumab ozogamicin and blinatumomab combined with low-intensity chemotherapy have shown promising results in two phase II studies in the same patient group [46][47][48].…”
Section: Discussionmentioning
confidence: 99%